Family and Peer Social Capital and Child Behavioral Outcomes in Japan - Jared M. Poff; Jonathan A. Jarvis; Mikaela J. Dufur; Shana L. Pribesh (MDPI AG, 2024)
Background/Objectives: Child problem behaviors have been linked to immediate and long-term negative outcomes. Research has found that family and peer social capital have a strong influence on child behavioral outcomes. However, most research about social capital and child behavior problems has been conducted in Western contexts. Social capital may influence child behavior problems differently in non-Western sociocultural environments due to different family and peer dynamics. Methods: Using a sample from the Japan Household Panel Survey and Japan Child Panel Survey (N = 182), we expand this literature on various forms of social capital to the Japanese context with data that were collected between 2009 and 2014. We examine the relationship of family and peer social capital with children internalizing and externalizing problem behaviors using OLS linear regression. Results: Our results differ from what is commonly found in Western contexts. Whereas family and peer social capital are typically associated with both internalizing and externalizing problem behaviors in Western countries, we find that greater family social capital is associated with decreased externalizing problem behaviors but not internalizing problem behaviors in Japan, and peer social capital has no association on either type of problem behaviors. Conclusions: Our findings emphasize the importance of considering social and cultural contexts when exploring how social capital might encourage prosocial child outcomes.